Contesting home defence : Men, women and the Home Guard in the Second World War - Summerfield, Penny; Peniston-Bird, C. M. (Book collections on Project MUSE., 2007)
Offering a new contribution to debates about the British home front in WWII, this book addresses the way the Home Guard has been remembered in popular culture through examination of key films, as well as TV's Dad's Army. The authors also explore the personal memories of individuals who served in the Home Guard.